Coagulation-flocculation of TiO2 in suspension used in heterogeneous photocatalysis - Santos, Jonilsom Moraes dos [UNESP]; Valente, José Pedro Serra [UNESP]; Jorge, Sônia Maria Alves [UNESP]; Padilha, Pedro de Magalhães [UNESP]; Saeki, Margarida Juri [UNESP]; Castro, Gustavo Rocha de [UNESP]; Florentino, Ariovaldo de Oliveira [UNESP] (My University, 2013)
The coagulation-flocculation of TiO2 in aqueous suspensions of low and intermediate ionic strength was investigated as a function of pH, of addition of aluminum sulfate and of stirring the suspension. This process was maximized after the addition of aluminum sulfate when the mixture was subjected to rapid and slow shaking and by using tap water at pH 7.0. Under these conditions, the turbidity of a suspension with 0.5 g L-1 of TiO2, which is higher than 4000 NTU, can be lowered to less than 10 NTU in 120 minutes. The filtration of the remaining suspension after coagulation-flocculation was 70 times faster than that of the initial suspension.
Keywords: Coagulation-flocculation; Aluminum sulfate; Titania